2021
DOI: 10.1080/17445302.2021.1907071
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of cavitating propeller underwater radiated noise using RANS & DES-based hybrid method

Abstract: This study focuses on the prediction of the hydrodynamic and hydroacoustic performance of a cavitating marine propeller in open water condition using Reynolds-averaged Navier-Stokes (RANS) and Detached Eddy Simulation (DES) solvers. The effectiveness of the methods is investigated for the recently introduced benchmark propeller that belongs to the research vessel 'The Princess Royal'. The main emphasis of the study is to examine the capabilities of the RANS and DES solvers for predicting the hydrodynamic perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…A very recent study, which was similar to the present investigation, compared the Newcastle round robin test case acoustic emissions for one operation point with the respective measurements from the University of Genoa (UNIGE) cavitation tunnel. The results obtained with DES and the Schnerr-Sauer cavitation model reached good agreement regarding the underwater noise signature between 100 Hz and 10 kHz [19].…”
Section: State Of the Artmentioning
confidence: 53%
“…A very recent study, which was similar to the present investigation, compared the Newcastle round robin test case acoustic emissions for one operation point with the respective measurements from the University of Genoa (UNIGE) cavitation tunnel. The results obtained with DES and the Schnerr-Sauer cavitation model reached good agreement regarding the underwater noise signature between 100 Hz and 10 kHz [19].…”
Section: State Of the Artmentioning
confidence: 53%
“…It should also be noted that comparisons between experiments and computations on the noise from marine propellers were rarely reported in the literature (for a few exceptions see Bensow & Liefvendahl 2016, Ebrahimi, Seif & Nouri-Borujerdi 2019, Sezen et al. 2020, Sezen, Atlar & Fitzsimmons 2021 a , Kimmerl et al. 2021 and Lidtke et al.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the deviations across experiments were often above the values of 20 dB shown in figure 20. It should also be noted that comparisons between experiments and computations on the noise from marine propellers were rarely reported in the literature (for a few exceptions see Bensow & Liefvendahl 2016, Ebrahimi, Seif & Nouri-Borujerdi 2019, Sezen et al 2020, Sezen, Atlar & Fitzsimmons 2021a, Kimmerl et al 2021and Lidtke et al 2022, where also similar or more significant deviations were found). Therefore, the results in figure 20 compare well with similar studies in the literature and can serve as a useful reference to assess the performance of high-fidelity simulations in matching acoustic measurements.…”
Section: Comparisons With the Experimentsmentioning
confidence: 99%
“…DES was used as opposed to RANS as it has been shown that the RANS solver does not capture the instabilities within the propeller wake flow [ 40 ], and in the case of tubercles, the suitability of the RANS solver has been questioned, especially in flow separation conditions [ 41 ]. In addition, it has been recommended to use high-fidelity solvers such as DES/LES when predicting the URN of marine propulsors [ 7 , 42 ]. The rotation rate was kept constant at 15rps and the advance velocity was varied to predict the open-water curve characteristics.…”
Section: Numerical Approachmentioning
confidence: 99%